ANALYSIS OF THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN INCLUSIVE SCHOOLS AT THE JUNIOR HIGH SCHOOL LEVEL IN PADANG CITY - Rezkia, Yusraini; Salma, Fitra; Rahmi, Lailatur; Rahmawati, Rahmawati; Afwina, Tiara Lingga; Rahmatika, Helsa (JPI (Jurnal Pendidikan Inklusi), 2024)
The implementation of inclusive education has many roles contained in it. Each role supports each other in order to create inclusive education for students. This research aims to find out how implementation of inclusive education in inclusive junior high school level in Padang City. Type of research carried out qualitative descriptive, with data collection techniques through direct interviews with Special Assistant Teachers (GPK) and supported by data obtained during field observations. Based on research that has been carried out, it was found that there are 4 types of Children with Special Needs (ABK) at this school for the 2022/2023 academic year, including blind, low vision, learning difficulties, and autism. This junior high school uses the regular (national) curriculum, namely the 2013 curriculum and the Independent Curriculum which has not been modified according to the needs and characteristics of students with special needs. In its implementation at this school there is an Individual Learning Program (PPI). Apart from that, this school also has a Special Assistant Teacher (GPK) in the learning process. The assessment techniques used are the same between ABK and regular students. In terms of School facilities and infrastructure already exist but are not yet optimal. Keywords: implementation, inclusive education, children with special needs